Young-of-the-Year Cod (Boreogadus) in Lancaster Sound and Western Baffin Bay - Sekerak, Aaron D. (ARCTIC, 1982)
Over 85% of all ichthyoplankton found in the study area in 1976 and 1978 were young-of-year (Y-O-Y) Boreogadus. Most of the remainder were seasnails (Cyclopteridae). Densities of Y-O-Y cod were related to season, depth, and (to a lesser degree) year and location. From June to at least mid-August, Y-O-Y cod were normally most abundant at 10-20 m depth and rare or absent at the immediate surface. Densities decreased below ~20 m and no Y-O-Y cod were caught at depths >250 m. After mid-August densities decreased at all depths sampled. More Y-O-Y cod may have been present in the study area in 1976 than in 1978, and Y-O-Y were significantly longer at a given date in 1976 than in 1978.Key words: arctic cod, Boreogadus, ichtyoplankton, larval fish, juvenile fish, growth, depth distribution, Lancaster Sound, Baffin Bay